Solution Delivery Process Framework for BMC Remedy Products - Škramlík, Jan; Pavlíček, Antonín, 1977-; Böhmová, Lucie; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2015)
The goal of this thesis is creation of methodology for repeatable transformation of customer business needs and goals resulting from company IT strategy to system functionality and process implementation in Business/IT Service Management projects using BMC Atrium and Remedy products. This methodology will be based on existing project management methodologies PRINCE2 and SCRUM. In the thesis I also refer to parts of ITIL v3 process framework. The aim of the thesis is to provide a project delivery framework for IT Consultancy organizations. The framework will foster efficient planning, tracking and communication of requirements and deliverables between IT Consultancy and their customer during entire project lifecycle and will therefore enable repeatable and consistent high quality delivery of customer success.
Vedoucí práce: Antonín Pavlíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: informační management [obor dipl. práce]; diplomové práce; master's theses